UEG week 2012 Report: Putting endoscopy into perspective - Papanikolaou, I. S. (Endoscopy, 2013)
The 20th United European Gastroenterology Week (UEG week; 20 – 24 October 2012; Amsterdam, The Netherlands) offered, once again, the opportunity for delegates interested in gastrointestinal endoscopy to update their knowledge as colleagues from all over the world shared their experiences. Various interesting studies on endoscopic topics were presented, allowing participants to become better acquainted with recent advancements and research trends in gastrointestinal endoscopy. This report focuses on oral presentations and selected poster presentations and aims to review them in the light of recent literature.